Costs Associated with the Treatment of Low Back Disorders: A Comparison of Surgeons and Physiatrists. Issue 6 (18th December 2019) - Standaert, Christopher J.; Li, Justin W.; Glassman, Stuart J.; Manolov, Nikolay E.; Thomas, Santhosh A.; Lee, Anthony A.; Dolak, Melanie A.; Stinneford, M. Kate
Abstract : Background: Spine care is costly and subject to wide variability. Defining costs and patterns of care for different specialties is critical to improving value. Objective: Determine costs, utilization, and differences therein for nonoperative and operative specialists in treating low back disorders. We hypothesized costs associated with nonoperative specialists would be lower. Design: Retrospective cohort. Setting: Medicare Limited Data Set (5% sample), 2011 to 2014. Participants: A total of 170 011 patients saw a primary care provider for a low back disorder between 1 July 2011, and 1 January 2013. Excluding those seen for a low back disorder in the preceding 6 months, final cohorts totaled 11 829 patients subsequently evaluated by a physiatrist (specialist in physical medicine and rehabilitation; 3183 patients) or surgeon (orthopedic or neurosurgeon; 8646 patients) within the following 6 months. Main Outcome Measures: Total Medicare expenditures, spine‐specific costs, spine surgical rates over 24 months. Results: Cohorts had comparable demographics, initial diagnoses, and baseline mean per‐member per‐month (PMPM) total spending. Mean 2‐year spine‐specific spending was $3978 for the physiatrist cohort and $7387 for the surgeon cohort. Comparatively, the physiatrist cohort had lower total mean 2‐year spine‐specific spending (−$3409; 95% confidence interval [CI] −$3824 to −$2994), mean PMPM total spending (−$122/mo; CI −$184 to −$60), and surgical rate (7.8% vs. 18.9%, risk ratio [RR] = 0.41; CI 0.36‐0.47). Surgery predominantly drove cost differential. Mean PMPM total spending for both cohorts remained elevated at 24 months compared to baseline mean spending (physiatrist: +$293; CI $447 to $138; surgeon: +$325; CI $425 to $225). Conclusions: Following a new episode of a low back disorder, substantial costs were seen for those subsequently evaluated by a physiatrist or surgeon. Costs were considerably lower for those first seen by a physiatrist. Patients in both cohorts displayed long‐term increases in health care costs. Our data suggest that early engagement in nonoperative care, when appropriate, may improve value.